To Assess the Time Taken to Provide Ideal Intubating Conditions during Rapid Sequence Intubation of Different Doses of Rocuronium Compared to Single Dose of Succinylcholine - Nishant Gautam; Dr. Sanskriti (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Aim: The aim of the present study was to assess the time taken to provide ideal intubating conditions during rapid sequence intubation of different doses of rocuronium compared to single dose of succinylcholine. Methods: This prospective, comparative randomized study was conducted at Rajindra hospital, Patiala. A total of 160 patient aged between 18-60 yrs of either gender and ASA physical status I and II who were scheduled to undergo elective surgery under general anaesthesia were divided under 4 categories with each category having 40 people [n=40]. Results: The demographics among the four groups were comparable. The comparison of intubating conditions at 60, 90 and 120 seconds was found to be statistically highly significant. The onset of action with rocuronium at 0.6, 0.9 and 1.2 mg/kg were 71.03 ± 24.05, 65 ± 21.9 and 51.30 ± 17.70 seconds and succinylcholine 39.78 +/- 8.04 seconds. Conclusion: Rocuronium at a dose of 1.2 mg/ kg is very effective and is a great asset to have during rapid sequence intubation. It provides adequate intubating conditions within a minute of injectio, avoiding the side effects of succinylcholine. So we recommend that rocuronium at a dose of 1.2 mg/kg is better than succinylcholine for the purpose of RSI.